Statistics : principles and methods - Johnson, Richard A. [ (Richard Arnold)] , 1937-; Bhattacharyya, Gouri K. , 1940- (John Wiley & Sons, 2014)
Statistics: Principles and Methods, 7th Edition provides a comprehensive, accurate introduction tostatistics for business professionals who need to learn how to apply key concepts. The chapters include real-world data, designed to make the material more relevant. The numerous examples clearly demonstrate the important points of the methods. New What Will We Learn opening paragraphs set the stage for the material being discussed. Using Statistics Wisely boxes summarize key lessons. In addition, Statistics in Context sections give business professionals an understanding of applications in which a statistical approach to variation is needed